The (Un)bearable Lightness of Being. The Cyrenaics on Residual Solipsism - Zilioli, Ugo (Peitho. Examina Antiqua, 2022)
The aim of this paper is to assess the evidence on Cyrenaic solipsism and show how and why some views endorsed by the Cyrenaics appear to be committing them to solipsism. After evaluating the fascinating case for Cyrenaic solipsism, the paper shall deal with an (often) underestimated argument on language attributed to the Cyrenaics, whose logic – if I reconstruct it well – implies that after all the Cyrenaics cannot have endorsed a radical solipsism. Yet, by drawing an illuminating parallel with Wittgenstein’s argument on private language and inner sensations, a case is to be made for the Cyrenaics to have subscribed to a sort of ‘residual solipsism’, which in turn helps us to understand the notion of Cyrenaic privacy at a fuller extent.